P192 Extreme body mass indices are frequent in inflammatory bowel disease patients and are associated with higher disease activity in Crohn`s disease, but not in ulcerative colitis: a cross-sectional analysis of the Swiss IBD cohort study. (16th January 2018) - Greuter, T; Porchet, F; Fournier, N; Biedermann, L; Schreiner, P; Scharl, M; Schoepfer, A; Safroneeva, E; Straumann, A; Rogler, G; Vavricka, S; ,
Abstract: Background: Obesity is a common phenomenon among patients with inflammatory bowel disease (IBD). On the other hand, malabsorption can result in a severe weight loss. The influence of extremes of body weight (BMI <17.5 and ≥30kg/m2) on disease course has yet to be determined. Methods: Data on all IBD patients included in the nation-wide Swiss IBD cohort study were analysed in a cross-sectional manner. Patients were classified into 3 different groups based on body mass index (BMI): group 1 BMI <17.5, anorexia; group 2 BMI 18.5–24.9, normal weight; group 3 BMI ≥30 kg/m2, obesity. The following outcome parameters were assessed: current disease activity (Crohn`s disease (CD): Crohn`s Disease Activity Index (CDAI), ulcerative colitis (UC): modified Truelove and Witts activity index), disease location, disease behaviour, quality of life (IBDQoL), and presence of extraintestinal manifestations (EIM) and complications (including fistula, stenosis, abscesses). 2-by-2 comparison was performed for extreme BMI groups vs. normal weight group. Results: We included a total of 2117 patients (1229 CD, 888 UC/IC): 67 patients had a BMI <17.5 (3.2%), 1725 a BMI 18.5–24.9 (81.5%), and 325 a BMI ≥30 kg/m 2 (15.4%). Compared with normal weight controls, anorexic patients were more often females (74.6 vs. 54.9%, p = 0.001) and more often had CD (86.6 vs. 56.6%, p < 0.001), while obese patients were older at diagnosis (median 32 vs. 26 years, p < 0.001). Anorexic and obese CD patients both had higher median CDAI scores (44 and 33 vs. 20, p < 0.001 and p = 0.001), with obese patients also showing increased stool frequency compared with normal weight controls (median soft stools 8 vs. 4/week, p = 0.001). No differences were seen regarding disease behaviour/location and The presence of fistula or abscesses. EIM were more frequent in obese CD patients (63.4 vs. 54.4%, p = 0.020), while anaemia (34.5 vs. 21.6%, p = 0.022) was more often seen in anorexic patients compared with normal weight patients. Faecal calprotectin was higher in anorexic (401 vs. 105 μg/g, p = 0.023), but not obese patients. Quality of life was globally affected in anorexic patients (IBDQoL 161 vs. 185, p < 0.001), while in obese patients this effect was only partially seen (decrease in the systemic and social, but not global score). In UC patients, no difference in disease activity was seen. Of note, anaemia was not more frequent in anorexic vs. normal weight patients, and quality of life was not decreased. Primary sclerosing cholangitis was less frequently reported in obese patients (0.8 vs. 5.5%, p = 0.014). Conclusions: In a large IBD cohort, prevalence of anorexia and obesity was 3.2 and 15.4%. Association between BMI and disease activity as well as quality of life was seen in CD, but not UC patients. These patients require close attention.